Clinical and ultrasonographic evaluation of shoulder in elite waterpolo players a cross-sectional study - Ruberti, A.; Ronga, M.; Callegari, L. (Research Square, 2020)
Background: Rotator cuff structural changes are common in overhead throwing athletes, such as baseball, javelin, swimming, volleyball, by increasing the risk of shoulder pain and injury. The structural alterations in elite waterpolo players are not well known. In elite waterpolo athletes there are structural alterations of rotato cuff tendons due to overuse of the dominant shoulder compared to the non-dominant, like in oth er overhead disciplines, identifiable by ultrasound (US). Methods: Asymptomatic elite men waterpolo players were selected. All athletes were evaluated with standardized scales of shoulder pain and function (Oxford Shoulder Score, Constant Shoulder Score) and provided data of training, injury and shoulder pain history. Each athlete underwent clinical evaluation of shoulders followed by US of rotator cuff, biceps and bursas. Results : 23 athletes met the inclusion criteria, mean age 24.2±3.3. 14 athletes (60.9%) presented higher degeneration grade at the dominant supraspinatus compared to the contralateral, always in the same area in outfield pla yers: anterior, lateral, pre-insertional. In 22/23 (95.6%) the biceps tendon was damaged: 20/23 athletes (87%) bilaterally, 2/23 (8.7%) at the only dominant limb. The site was always at the bicipital groove in its insertion on the humerus. Power Doppler (PD) evidenced neovascularization in only 5/23 (21.7%) players at supraspinatus: 4 bilaterally, 1 only at the non-dominant. No statistical correlation was found between tendon degeneration and age, career years. Conclusion: Outfield waterpolo players have peculiar changes in supraspinatus at preinsertional level, as seen in other overhead throwing athletes. We found changes also in biceps, bilaterally, like in shoulders of elite swimmers. We suppose that these changes are predictive of shoulder pain and injury.